Recurrent urethral obstruction in a male Persian cat - Zamzami, Rumi Sahara; Yuliansyah, Nanda; Ferdian, Riyan; Hasan, M; Sari, Wahyu Eka (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
Recurrent urethral obstruction (rUO) is a critical condition predominantly affecting male Persian cats, necessitating urgent veterinary care due to its high morbidity and potential mortality. This case report details a five-year-old male Persian cat with a history of five episodes of urethral obstruction, despite neutering after the second incident. The cat presented with symptoms including excessive straining and inappropriate urination. Diagnostic evaluations involved physical examination, urinalysis, urine sedimentation, radiography, and ultrasonography. Laboratory results revealed abnormalities such as elevated leukocyte count, blood, protein, nitrites, and struvite crystals in the urine. Radiographic and ultrasonographic imaging indicated an enlarged and firm urinary bladder with no visible stones, but a thickening of the bladder wall and crystal accumulation were noted. The management strategy included immediate relief of obstruction via catheterization and long-term dietary adjustments, though the cat's habit of consuming non-prescribed food contributed to recurrent episodes. This report highlights the challenges in managing rUO in Persian cats and emphasizes the importance of comprehensive diagnostic procedures, strict dietary management, and ongoing monitoring to prevent recurrence. The findings contribute to the existing literature on feline lower urinary tract diseases (FLUTD) and offer insights for veterinarians in clinical practice, suggesting that prolonged catheterization and strict adherence to a specialized urinary diet may reduce recurrence rates and improve outcomes for affected cats.